A pyroptosis-associated signature plays a role in prognosis prediction in clear cell renal cell carcinoma - Zhiyuan Li; Zhinan Xia; Yipeng Yu; Licheng Cai; Wengang Jian; Tengda Wang; Wei Xue; Xingyuan Wang; Bowen Wang; Peng Zhang; Wenhao Yao; Cheng Zhang; et al. (BMC, 2022)
Abstract Background Approximately 90% of renal malignancies are RCCs (renal cell carcinomas), and the primary subtype in histology is ccRCC (clear cell RCC). In recent years, pyroptosis has been considered a kind of inflammation-related programmed cell death that participates in the invasion, metastasis, and proliferation of tumour cells, thereby influencing tumour prognosis. Nonetheless, the expression level of pyroptosis-associated genes in RCCs and their relationship with prognosis remain obscure. Results In our research, 44 regulators of pyroptosis that were differentially expressed between normal kidney and ccRCC tissues were identified. ccRCC cases were categorized into 2 subgroups according to prognostic-related DEGs (differentially expressed genes), and there was a significant difference in OS (overall survival) between them. The prognostic value of pyroptosis-associated genes was assessed as a signature based on a cohort from TCGA (The Cancer Genome Atlas). Following Cox regression with DEGs and LASSO (least absolute shrinkage and selection operator), a 6-gene signature was established, and all ccRCC cases in the cohort from TCGA were categorized into an LR (low-risk) or HR (high-risk) group (P < 0.001). In combination with clinical features, risk scores were considered a predictive factor of OS in ccRCC. KEGG (Kyoto Encyclopedia of Genes and Genomes) and GO (Gene Ontology) analyses suggest increased immunity and enrichment of genes related to immunity in the HR group. Conclusions Our findings indicate that genes related to pyroptosis have an important role in tumour immunity and may be used to predict the prognosis of ccRCC.